Strategi Komunikasi Sosial Media Buzzer @infodenpasar Pada Instagram Dalam Menyebarkan Informasi dan Membangun Opini Masyarakat Kota Denpasar - Ulio, Ulio; Saskara, I Putu Adi; Dharma, I Wayan Yudhasatya (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
This research is a qualitative research that examines the Social Media Buzzer @Infodenpasar Communication Strategy on Instagram in disseminating information and building public opinion in Denpasar City. This research is very important because in today's digitalization era, the use of information technology is to facilitate the public in all lines of activity and the flow of information dissemination and exchange is very fast which often causes uproar in cyberspace because of the rampant circulation of hoax or fake news, an account is present. @infodenpasar on Instagram as a social media buzzer with 885 thousand followers / followers to become credible and trusted news and information presenter accounts in spreading news and information about Denpasar City. In this study, the focus will be on analyzing three problems, namely: (1) Why do the people of Denpasar City choose social media buzzer @infodenpasar account on Instagram in looking for news and information about the city of Denpasar ?, (2) How is the social media buzzer @infodenpasar communication strategy on Instagram in disseminating information and building public opinion in Denpasar City, (3) What are the implications of social media buzzer @infodenpasar on Instagram in spreading information and building public opinion in Denpasar City?The research method used is a qualitative research method, to achieve the research objectives, relevant and adequate data are required. Researchers as a key instrument, the technique of determining informants using a purposive sampling model, while the data collection techniques used observation, interviews and library studies.The findings of the study include: Reasons for social media users in choosing the @infodenpasar account as a media in searching for news and information about the city of Denpasar, consumer behavior through several stages of the decision making process, namely information search, alternative evaluation, and purchase decisions The communication strategy used by @infodenpasar is by using redundancy techniques, canalizing techniques, informative techniques, and persuasive techniques. Furthermore, the implications for the communication strategy of the Social Media Buzzer @infodenpasar in disseminating information and building public opinion in the city of Denpasar include: Implications for Community Economic Development, Implications for Easing Access to Education, Implications for Forming Ethics and Decency, and Implications for Safety and Smooth Traffic.Â